Combining science and faith for better quality and safety in halalan toyyiban products - Azmi, Nor Azrini Nadiha; Najihah Mohd Noor; Amal Elgharbawy; Noviyan Darmawan (Halal Studies and Society, 2024)
Halalan Toyyiban, a concept rooted in Islamic teachings, is focused on quality, safety, ethical considerations, and permissibility. "halal" is defined as items permissible under Islamic law, while "toyyib" ensures the items are pure, wholesome, and ethically sourced. This concept, derived from the Quran and Sunnah of the Prophet Muhammad (PBUH), provides a comprehensive framework for guiding Muslim practices. In global marketplace, integrating scientific methods with halalan toyyiban principles is becoming increasingly important, particularly in the food, cosmetics, and pharmaceutical industries. Scientific methods offer effective tools for verifying the halal status of products and enhancing the toyyib attributes. This integration helps ensure that products meet both Islamic and modern standards, thereby strengthening the credibility of halal certifications through evidence-based practices. Techniques, such as chromatography, DNA testing, and mass spectrometry, were commonly adopted to detect non-halal contaminants and verify product integrity. These innovations reassures consumers that the products are religiously permissible and meet high standards of safety and ethical production.